Finite element modeling of fabric-tying based on Arimatsu Narumi Shibori Robot. (January 2023) - Shinohara, Kazunori; Nishibori, Kenji
Arimatsu Narumi Shibori (thread-tying), which is a traditional craft, has a history of more than 400 years and has been handed down to artisans in Japan. Recently, the shortage of successors to artisans has emphasized the maintenance of this thread-tying technique. To achieve this, Arimatsu Narumi Shibori needs to be elucidated based on scientific knowledge using numerical analysis techniques, which has not been achieved so far. In this technique, the fabric is complexly deformed, and complex wrinkles are formed in it. One possible approach for modeling this fabric is the use of a shell element that does not have an element volume. As the tensile and bending stiffnesses of the shell element are evaluated using a single Young's modulus, the bending stiffness increases with the tensile stiffness. Therefore, unlike the deformation achieved by the actual fabric-tying, this fabric analysis model cannot achieve large deformation of the fabric. In this study, a tying analysis method is proposed to elucidate Arimatsu Narumi Shibori. In this method, the fabric is modeled using three layers of shell elements to reproduce the fabric behavior. The material properties of the three-layer structure are presented based on the tensile test, the bending test and the friction test. Using the proposed method, we could visualize the stress distribution and wrinkles in the fabric-tying and elucidate its breaking condition.